The impact of galactooligosaccharides on the bioaccessibility of sterols in a plant sterol-enriched beverage: adaptation of the harmonized INFOGEST digestion method. Issue 4 (29th March 2018) - Blanco-Morales, Virginia; López-García, Gabriel; Cilla, Antonio; Garcia-Llatas, Guadalupe; Barberá, Reyes; Lagarda, María Jesús; Sánchez-Siles, Luis Manuel; Alegría, Amparo
Abstract : Bioaccessibility of sterols in milk-based fruit beverages: comparison of two in vitro digestions. Abstract : The effect of the addition of galactooligosaccharides (GOS) on sterol bioaccessibility in three plant sterol (PS)-enriched milk-based fruit beverages (without GOS addition (MfB) and with 2.5 g (MfB-G2 ) and 5.0 g (MfB-G5 ) GOS per 250 mL) was evaluated after micellar gastrointestinal digestion. Cholesterol bioaccessibility was very similar among beverages, though a slight significant increase (from 80% to 85%) was observed by the addition of 5.0 g GOS. The addition of GOS did not affect total PS bioaccessibility (≈37%). Based on the results obtained after micellar digestion, it has been demonstrated that these beverages could be a suitable food matrix for simultaneous enrichment with PS and GOS. The harmonized in vitro digestion model INFOGEST was applied to the MfB beverage, but the cholesterol content could not be quantified due to its contribution of bile salts. Hence, it was proposed: (i) a change in porcine bile salt concentration from 10 mM to 1.4 mM (in order to compare with micellar digestion); or (ii) a change of bile salt origin (bovine instead of porcine), maintaining physiological concentration (10 mM, INFOGEST condition). Both options allowed cholesterol quantification, with bioaccessibilities of 62% (reduction of bile salts) and 38% (replacement of the bile salt source), whereas plant sterol bioaccessibilities were 22% and 14%, respectively. Therefore, the change of bile salt origin maintaining INFOGEST concentration is proposed as a method to evaluate sterol (cholesterol and PS) bioaccessibility in these beverages, demonstrating the need for the selection of appropriate conditions of the INFOGEST harmonized method according to the food matrix and compounds to be determined.